Hot subdwarf stars and their connection to thermonuclear supernovae - Geier, S.; Kupfer, Thomas; Ziegerer, Eva; Heber, Ulrich; Nemeth, Peter; Irrgang, Andreas (Journal of Physics: Conference Series, 2016)
Hot subdwarf stars (sdO/Bs) are evolved core helium-burning stars with very thin hydrogen envelopes, which can be formed by common envelope ejection. Close sdB binaries with massive white dwarf (WD) companions are potential progenitors of thermonuclear supernovae type Ia (SN Ia). We discovered such a progenitor candidate as well as a candidate for a surviving companion star, which escapes from the Galaxy. More candidates for both types of objects have been found by crossmatching known sdB stars with proper motion and light curve catalogues. The Gaia mission will provide accurate astrometry and light curves of all the stars in our hot subdwarf sample and will allow us to compile a much larger all-sky catalogue of those stars. In this way we expect to find hundreds of progenitor binaries and ejected companions.
CRIS-Team Scopus Importer:2020-12-21